Silver Age’s Paradoxes: Unamuno and Pérez de Ayala Interpreted by Ortega’s La deshumanización del arte and Guillén, Illustrator of Meditaciones del Quijote - Wiesse Rebagliati, Jorge (2025)
A crossed chronology paradoxically connects several works from the Silver Age of Spanish Literature: Niebla (1914) by Miguel de Unamuno with La deshumanización del arte (1925) by José Ortega y Gasset; and Meditaciones del Quijote (1914) by José Ortega y Gasset with Cántico (1936) by Jorge Guillén. Likewise, a distant Ramón Pérez de Ayala, in Tigre Juan. El curandero de su honra (1926), becomes —consciously or not—an earnest executor of the ideal of the psychological novel proposed by José Ortega y Gasset in Ideas sobre la novela (1925) and of some characteristics of modern aesthetics outlined in La deshumanización del arte. This paper aims to map the relations —whether present or absent— of Ortega y Gasset’s aesthetic ideas within his own generation, as well as those that preceded and followed it..